2021
DOI: 10.1111/jcal.12548
|View full text |Cite
|
Sign up to set email alerts
|

Visual representation fidelity and self‐explanation prompts in multi‐representational adaptive learning

Abstract: In their prior research on adaptive instruction for multi‐representational learning, the researchers explored various perspectives on designing visual representations and scaffolds. However, controversies and discrepancies regarding the fidelity of visual representations and self‐explanation prompts have yet to be resolved. This research thus examines types of visual representations and self‐explanation prompts and thereby suggests instructional strategies for multi‐representational adaptive learning. Sixty‐ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
(129 reference statements)
1
2
0
1
Order By: Relevance
“…The performance of learners in different languaging conditions was significantly different in the delayed test. This result corroborates the findings in cognitive psychology (e.g., Joo et al., 2021; Martin et al., 2022). Table 10 reveals that prompted written languaging was more predictive of learning than both the two modes of oral languaging.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The performance of learners in different languaging conditions was significantly different in the delayed test. This result corroborates the findings in cognitive psychology (e.g., Joo et al., 2021; Martin et al., 2022). Table 10 reveals that prompted written languaging was more predictive of learning than both the two modes of oral languaging.…”
Section: Discussionsupporting
confidence: 92%
“…In cognitive psychology, it has been proved that the prompts for self-explanation can affect learning. For example, Joo et al (2021) found that learners receiving prompts fading from full to less scaffolding achieved significantly higher knowledge inference scores than learners receiving prompts delivering fixed instructions. Martin and colleagues (2022) found that focused prompts explicitly activating relevant constructs and terms in learning materials helped pre-service teachers notice more tutoring strategies than open prompts without particular guidance.…”
Section: Mode Of Languagingmentioning
confidence: 99%
“…As Menendez et al (2022) describe that visual abstraction may have more positive effects on adults than on children in transfer tasks, it may also be worthwhile to investigate whether the present results can likewise be affected by age or other learner characteristics, such as spatial ability (Brucker et al, 2014; Huk, 2006). In addition, the combination of rendering styles and fading of realistic details that have been shown to enhance learning (Fyfe et al, 2014; Joo et al, 2021) should be assessed in a task in which concrete surface details need to be mentally transformed in a way similar to the present studies. Finally, it needs to be assessed whether the findings of the studies have an impact on dynamic visualizations, animations, and learning in virtual reality.…”
Section: Discussionmentioning
confidence: 99%
“…Інформаційна навчальна система для адаптивного навчання інформатики та математики повинна забезпечувати умови для досягнення навчальних цілей; поєднувати різні типи подання навчальних матеріалів з урахуванням індивідуальних особливостей здобувачів освіти щодо сприйняття матеріалу (візуал, аудіал або кінестетик), бути адаптована під різні форми й методи навчання [26][27].…”
Section: результати дослідженняunclassified